Kinerja Operasional Kapal Pelayaran Rakyat di Pelabuhan Pare-Pare - Makmur Syam; Poerwanto Poerwanto (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The role of people's shipping or traditional ships as a means of sea transportation is needed to encourage and encourage economic development in underdeveloped areas. This study aims to identify the operational performance of people's shipping vessels at the Port of Pare-Pare. This research was conducted with a qualitative method through semi-structured interviews with the aim of obtaining in-depth information from respondents regarding information on the operational performance of people's shipping vessels and community perceptions regarding the operational performance of these people's shipping vessels. After looking at the discussion presented, it can be concluded that the provision of transportation depends on the supply function. This function describes the correlation between the amount of goods offered by the market and the price level offered. The number of transportation services available depends on several factors, including vehicle capacity, road and terminal capacity, as well as the level and quality of management.